EARLY DETECTION OF CANCER: WARNING SIGNALS FROM THE BODY (Лучшие интеллектуальные исследования, 2025)
Abstract: Early detection plays a critical role in the successful treatment and survival of cancer patients. The human body often sends subtle warning signals long before the disease becomes life-threatening. This article explores the common early symptoms associated with various types of cancer, the importance of early screening, and the role of awareness in timely diagnosis. The findings emphasize that recognizing these warning signs can drastically improve outcomes and reduce cancer mortality.